Catalyst for reductive amination of aldehyde ketone compounds as well as preparation method and application of catalyst

The metal particle catalyst is encapsulated by all-silicon molecular sieve, and the problem of insufficient conversion rate and selectivity in the reduction amination reaction of aldehyde ketone compounds in the prior art is solved, and high-efficiency primary amine generation and catalyst stability are achieved, and by-products are reduced. Generation of .

CN119186628AActive Publication Date: 2024-12-27TIANJIN UNIV

Patent Information

Application Number
CN202310766853.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-27
Publication Date
2024-12-27
Estimated Expiration
2043-06-27

AI Technical Summary

Technical Problem

In the reduction amination reaction of aldehyde ketone compounds, the conversion and selectivity of the existing catalysts are insufficient, and the metal catalyst is unstable, easy to oxidize and burn, and it is difficult to effectively generate efficient primary amines.

Method used

The metal particle catalyst is encapsulated using a full silicon molecular sieve. The metal particles are distributed inside the molecular sieve. The nanocatalyst is formed through a specific preparation method, including mixing silicon-containing substances, alkyl ammonium hydroxide and metal particle precursors, and passing through sol gel, preliminary Crystallization, washing, calcination and reduction steps to prepare a catalyst with excellent catalytic activity and structural stability.

Benefits of technology

The conversion rate of aldehyde ketone compounds and the selectivity of target products is improved, the conversion rate of catalytic furfural and benzaldehyde reaches 100%, and high selectivity is maintained, the stability of the catalyst is improved, and the generation of by-products is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186628A_ABST
    Figure CN119186628A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for reductive amination of aldehyde ketone compounds as well as a preparation method and application of the catalyst. The catalyst comprises an all-silicon molecular sieve and metal particles, the metal particles are distributed in the all-silicon molecular sieve; the average linear size of crystal grains of the catalyst is 50-100 nm; the particle size of the metal particles is 0.5-4 nm; on the basis of the mass of the catalyst, the mass percentage content of the metal particles is 0.1-10wt%; metal elements in the metal particles are selected from at least one of Pd, Pt, Rh, Cu, Ni, Co, Zn and Ag. The catalyst provided by the invention can be applied to reductive amination reaction of aldehyde ketone compounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst, in particular to a catalyst for reductive amination of aldehyde and ketone compounds, and a preparation method and application thereof. Background Art

[0002] Primary amines are important chemical substances that are widely used in the synthesis of dyes, agrochemicals, pharmaceuticals, detergents, and polymers. There are several synthetic methods for primary amines, such as the reductive amination of carbonyl compounds and alcohols, the hydrogenation amination of olefins, the amination of aryl halides, and the reduction of specific nitrogen sources (amides, nitriles, and nitro compounds). Among these methods, ammonia (NH 3 ) is a nitrogen source, H 2 Reductive amination of carbonyl compounds (ketones or aldehydes) as reducing agents is a particularly cost-effective and atom-efficient method that can largely reduce the formation of by-products.

[0003] Taking the process of furfural reductive amination to tetrahydrofurfurylamine as an example, the aldehyde group first reacts with ammonia to form a primary imine, and then the primary imine reacts with hydrogen under the action of a metal catalyst to form furfurylamine and / or tetrahydrofurfurylamine. In this process, in order to improve the selectivity of tetrahydrofurfurylamine, it is necessary to use a metal with strong hydrogenation ability to hydrogenate the carbon-carbon double bond, while also minimizing the further hydrogenation of Schiff base to form coupling products such as difurfurylamine and ditetrahydrofurfurylamine (see reference: Energy Environ. Sci., 2016, 9, 1144-1189).

[0004] US4598159 discloses a method for reducing and aminating furfural to tetrahydrofurfurylamine using furfural as raw material, dioxane and tetrahydrofurfurylamine as solvents, using Raney nickel to catalyze the hydrogenation of furfural to form tetrahydrofurfurylamine at 150°C and 3MPa H 2 After 6 hours of reaction under the reaction conditions, the furfural conversion rate reached 100%, and the tetrahydrofurfurylamine selectivity was 89%. In the process, tetrahydrofurfurylamine was used as a solvent, and secondary and tertiary amine by-products were inevitably introduced. There is also a literature (Catal. Sci. Technol., 2017, 7, 4129-4135) reporting the use of furfural as a raw material, tetrahydrofuran as a solvent, and the use of Raney nickel to catalyze the hydrogenation reduction amination of furfural to tetrahydrofurfurylamine at 180°C and 1MPa H 2 After 48 hours of reaction under the reaction conditions, the furfural conversion rate reached 98.2% and the tetrahydrofurfurylamine selectivity was 95.7%.

[0005] CN105481701A discloses a method for preparing an itopride intermediate, using water as a solvent, p-hydroxybenzaldehyde, alkali, and ammonia water, and hydrogenating and reducing them under the action of Raney nickel to obtain p-hydroxybenzylamine. However, the Raney nickel catalyst is unstable and easily oxidized and burned in the air.

[0006] Therefore, it is of great significance to develop highly active and selective heterogeneous catalysts for the production of primary amines.

[0007] CN115487825A discloses a furfural reduction amination catalyst and a preparation method thereof. The catalyst is represented by M 1 / M 2 M 3 AlOx, of which: M 1 is the noble metal active component, M 2 M 3 AlOx is the carrier; M 1 The loading amount is 0.1-1wt%; M 1 The average particle size is 2.4-2.8nm and the dispersion is 40-50%. 2 M 3 AlOx is composed of hydrotalcite M 2 M 3 The composite metal oxide is formed by Al-LDHs topology, wherein the coordination structure of Al includes four-coordinate and six-coordinate, and the ratio of four-coordinate aluminum to six-coordinate aluminum is 40-60%.

[0008] Metal / molecular sieve catalysts have gradually become a research hotspot in recent years. They can combine the characteristics of metals with the advantages of molecular sieve pore selectivity and are widely used in reactions such as biomass catalytic conversion, phenol catalytic deoxygenation, and catalytic reforming.

[0009] CN111054432A discloses a catalyst for preparing hexamethylenediamine, a preparation method and application thereof. The catalyst is a noble metal catalyst encapsulated in HZSM-5 molecular sieve, which is used as a catalyst to catalyze the reductive amination of adipaldehyde to prepare hexamethylenediamine. Summary of the invention

[0010] In view of this, an object of the present invention is to provide a catalyst for the reductive amination of aldehyde and ketone compounds, which contains an all-silicon molecular sieve and metal particles, and can be used for the reductive amination of aldehyde and ketone compounds to generate primary amines, especially for the reductive amination of furfural and benzaldehyde. The conversion rate and selectivity are high. Another object of the present invention is to provide a method for preparing the catalyst. Another object of the present invention is to provide the application of the catalyst. The present invention achieves the above-mentioned objects through the following technical solutions.

[0011] In one aspect, the present invention provides a catalyst for reductive amination of aldehyde and ketone compounds, which comprises an all-silicon molecular sieve and metal particles; wherein:

[0012] The metal particles are distributed inside the all-silicon molecular sieve;

[0013] The average linear size of the catalyst crystals is 50 to 100 nm;

[0014] The particle size of the metal particles is 0.5-4 nm; based on the mass of the catalyst, the mass percentage of the metal particles is 0.1-10 wt%; the metal element in the metal particles is selected from at least one of Pd, Pt, Rh, Cu, Ni, Co, Zn and Ag. Such a catalyst can be used as a catalyst in the reduction amination reaction of aldehydes and ketones, which can improve the conversion rate of raw materials and the selectivity of target products.

[0015] In the present invention, the average linear size refers to the mean value of the linear size of the grains in the SEM image, that is, the average value of the particle size of the grains.

[0016] The catalyst of the present invention is a metal particle catalyst encapsulated in an all-silicon molecular sieve, and the metal particles are distributed inside the molecular sieve. The metal particles are basically evenly distributed inside the all-silicon molecular sieve. In the present invention, the aluminum oxide content of the all-silicon molecular sieve is basically zero, and it can also be called Silicalite-1 molecular sieve.

[0017] The particle size of the metal particles is 0.5 to 4 nm, preferably 1 to 3 nm, for example, 2 nm, 2.5 nm, 3 nm, 3.5 nm or 4 nm.

[0018] Based on the mass of the catalyst, the mass percentage of the metal particles is 0.1-10wt%, preferably 0.2-8wt%. For example, it can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 1.0wt%, 2.0wt%, 3.0wt%, 5.0wt% or 7.0wt%. Such a catalyst can not only improve the conversion rate of the raw material, but also maintain a high selectivity of the target product.

[0019] The average linear size of the catalyst crystallites is 50 to 100 nm, preferably 50 to 90 nm, for example, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm.

[0020] The catalyst of the invention is formed by stacking hexagonal prism-like crystal grains with a size of about 80 nm. The crystal grains are uniform in size and have a relatively large specific surface area, which is beneficial to increasing reaction sites and improving mass transfer rate. The catalyst has excellent catalytic activity and structural stability when used in catalyzing the reduction amination reaction of carbonyl compounds ketones or aldehydes. In the process of catalyzing the reduction amination reaction of furfural, the conversion rate of furfural can reach 100%, and the catalyst also has high selectivity for the product tetrahydrofurfurylamine. In the process of catalyzing the reduction amination reaction of benzaldehyde, the conversion rate of benzaldehyde can reach 100%, and the catalyst also has significantly improved selectivity for the product benzylamine.

[0021] The catalyst of the present invention is formed by raw materials including a metal particle precursor and a silicon-containing substance capable of forming an all-silicon molecular sieve; wherein the metal particle precursor includes a water-soluble metal salt, preferably a water-soluble metal salt-ethylenediamine complex solution. The silicon-containing substance is selected from silicate or alkaline silica sol.

[0022] According to the catalyst of the present invention, preferably, the morphology of the catalyst crystal particles is substantially hexagonal, which is conducive to increasing the specific surface area.

[0023] According to the catalyst of the present invention, preferably, the metal element in the metal particles is selected from one of Pd, Pt, Rh, Cu and Ni. More preferably, it is selected from one of Pd, Pt and Rh. This is beneficial to improve the conversion rate of raw materials and the selectivity of target products in the reductive amination reaction of aldehydes and ketones.

[0024] On the other hand, the present invention also provides a method for preparing the catalyst as described above, comprising the following steps:

[0025] 1) mixing a silicon-containing substance, alkylammonium hydroxide, a metal particle precursor and water and stirring at 20 to 45° C. to obtain a sol-gel;

[0026] 2) Preliminarily crystallizing the obtained sol-gel at 70-100° C. to form nuclei, then heating to 160-180° C. to continue crystallization, and separating the solid and liquid to obtain a solid;

[0027] 3) washing the obtained solid, drying it, calcining it at 500-600° C., and then reducing it in a hydrogen atmosphere at 350-450° C. to obtain the catalyst;

[0028] in,

[0029] The silicon-containing substance is selected from silicate or alkaline silica sol; the alkyl ammonium hydroxide is selected from at least one of tetramethyl ammonium hydroxide, tetraethyl ammonium hydroxide, tetrapropyl ammonium hydroxide, dimethyl diethyl ammonium hydroxide and dimethyl dipropyl ammonium hydroxide; the metal particle precursor is a water-soluble metal salt-ethylenediamine complex solution;

[0030] The molar ratio of silicon element, alkylammonium hydroxide and water in the silicon-containing substance is 1:0.1-0.4:15-25;

[0031] The molar ratio of the metal element in the water-soluble metal salt to the silicon element in the silicon-containing substance is 0.0004 to 0.055: 1. This is conducive to obtaining a fully silicon molecular sieve encapsulated metal particle catalyst with a specific morphology and particle size suitable for the reductive amination reaction of aldehyde or ketone compounds.

[0032] In the present invention, the silicon-containing material is selected from silicate or alkaline silica sol, preferably silicate. The silicate is selected from at least one of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate, and butyl orthosilicate, preferably ethyl orthosilicate.

[0033] The alkylammonium hydroxide is preferably tetrapropylammonium hydroxide.

[0034] The molar ratio of silicon in the silicon-containing substance to alkylammonium hydroxide can be 1:0.1-0.4, preferably 1:0.2-0.3. The molar ratio of silicon to water can be 1:15-25, preferably 1:18-24, more preferably 1:19-21, for example 1:20. The molar ratio of the metal element in the water-soluble metal salt to the silicon in the silicon-containing raw material can be 0.0004-0.055:1, preferably 0.0004-0.045:1, so that the mass percentage of the metal particles in the catalyst formed can be 0.1-10wt% based on the mass of the catalyst.

[0035] In the present invention, the washing is preferably performed with water, preferably until the pH value of the washing liquid is 7 (ie neutral).

[0036] According to the preparation method of the present invention, preferably, the silicate is selected from at least one of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate and butyl orthosilicate.

[0037] According to the preparation method of the present invention, preferably, the silicate is ethyl orthosilicate.

[0038] According to the preparation method of the present invention, preferably, the alkylammonium hydroxide is tetrapropylammonium hydroxide.

[0039] The preparation method according to the present invention preferably comprises the following specific steps:

[0040] 1) mixing a silicon-containing substance, alkylammonium hydroxide, a water-soluble metal salt-ethylenediamine complex solution and water and stirring at 20 to 45° C. for 6 to 12 hours to obtain a sol-gel;

[0041] 2) preliminarily crystallizing the obtained sol-gel at 70-100° C. for 24-48 hours to form nuclei, then heating to 160-180° C. to continue crystallization for 12-72 hours, and performing solid-liquid separation to obtain a solid;

[0042] 3) washing the obtained solid, drying it, calcining it at 500-600° C. for 3-12 h, and then reducing it in a hydrogen atmosphere at 350-450° C. for 1.5-4 h to obtain the catalyst.

[0043] The present invention finds that in the step of obtaining the sol-gel, the amount of water and the temperature range need to be controlled. If the amount of water and the temperature range are not within the scope of the present invention, it is not conducive to the formation of a nanocatalyst for the reductive amination of aldehydes and ketones.

[0044] The present invention finds that the time of initial crystallization nucleation should not be too short or too long, which will affect the formation of nanocatalysts. The temperature of initial crystallization nucleation should not be too high or too low, which will also affect the formation of nanocatalysts.

[0045] In step 1), the mixing temperature is 20 to 45° C., preferably 20 to 40° C., such as 30° C. or 35° C. The stirring time may be 6 to 12 hours, preferably 8 to 10 hours. The feed ratio of each substance is as described above and will not be described in detail here.

[0046] In step 2), the temperature of the initial crystallization nucleation can be 70 to 100° C., preferably 75 to 95° C., and more preferably 80 to 90° C. The time of the initial crystallization nucleation can be 24 to 48 hours, preferably 24 to 36 hours. The temperature of the continued crystallization can be 160 to 180° C., preferably 170 to 175° C. The time of the continued crystallization can be 12 to 72 hours, preferably 20 to 72 hours, for example 70 to 72 hours. The solid-liquid separation can be centrifugal.

[0047] In step 3), the drying temperature can be 100-120°C, preferably 105-110°C. The drying time can be 2-10h, preferably 4-8h. During roasting, the heating rate can be controlled to be 1.5-7°C / min, preferably 2-4°C / min. The roasting temperature can be 500-600°C, preferably 520-570°C, for example, 550°C. The roasting time can be 3-12h, preferably 6-10h. After roasting, the temperature is lowered to 30-50°C. Then the heating rate can be controlled to heat up to the temperature for the next reduction. The heating rate can be 2-11°C / min, preferably 3-5°C / min. The temperature of reduction under a hydrogen atmosphere can be 350-450°C, preferably 380-420°C, for example, 400°C. The reduction time can be 1.5-4h, preferably 2-3h.

[0048] In another aspect, the present invention also provides use of the catalyst as described above as a catalyst for the reductive amination of aldehydes and ketones.

[0049] According to the application of the present invention, preferably, the aldehyde and ketone compounds include furfural and benzaldehyde; the target product of the reductive amination of furfural is tetrahydrofurfurylamine; the target product of the reductive amination of benzaldehyde is benzylamine. In certain preferred embodiments, the aldehyde and ketone compounds are selected from furfural or benzaldehyde.

[0050] The catalyst of the present invention is a nano catalyst, which includes an all-silicon molecular sieve and metal particles, and the metal particles are distributed inside the all-silicon molecular sieve. It can be used as a catalyst in the reduction amination reaction of aldehyde and ketone compounds, so that the selectivity of the target product is higher and the conversion rate of the raw material aldehyde and ketone compounds is higher. The preparation method of the present invention can obtain a catalyst for the reduction amination of aldehyde and ketone compounds with a specific morphology and particle size. According to the preferred technical scheme of the present invention, the present invention adopts a silicon-containing material, tetrapropylammonium hydroxide, water and a complex solution of a water-soluble metal salt-ethylenediamine, and controls their dosage within a specific range, as well as controls the temperature and crystallization nucleation time, so that the nano catalyst of the present invention with a specific morphology suitable for the reduction amination of aldehyde and ketone compounds can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 is the X-ray diffraction pattern of the catalyst prepared in Example 1 of the present invention;

[0052] Figure 2 is a SEM image of the catalyst prepared in Example 1 of the present invention;

[0053] Figure 3 is a TEM image of the catalyst prepared in Example 1 of the present invention;

[0054] Figure 4 is the X-ray diffraction pattern of the catalyst prepared in Example 3 of the present invention;

[0055] Figure 5 is a SEM image of the catalyst prepared in Example 3 of the present invention;

[0056] Figure 6 is a TEM image of the catalyst prepared in Example 3 of the present invention;

[0057] Figure 7 is the X-ray diffraction pattern of the catalysts prepared in Examples 4, 5, 6, 7, 8 and 9 of the present invention;

[0058] Figure 8 is the X-ray diffraction pattern of the catalyst prepared in Comparative Example 1 of the present invention;

[0059] Fig. 9 is a SEM image of the catalyst prepared in Comparative Example 1 of the present invention;

[0060] Fig.10 is the X-ray diffraction pattern of the catalyst prepared in Comparative Example 2 of the present invention;

[0061] Fig.11 is a SEM image of the catalyst prepared in Comparative Example 2 of the present invention;

[0062] Fig.12 is a TEM image of the catalyst prepared in Comparative Example 2 of the present invention;

[0063] Fig.13 is the X-ray diffraction pattern of the catalyst prepared in Comparative Examples 3, 4 and 5 of the present invention;

[0064] Fig.14 is a SEM image of the catalyst prepared in Comparative Example 3 of the present invention;

[0065] Fig.15 is a SEM image of the catalyst prepared in Comparative Example 4 of the present invention;

[0066] Fig.16 is a SEM image of the catalyst prepared in Comparative Example 5 of the present invention. DETAILED DESCRIPTION

[0067] <Analysis Method>

[0068] The following describes the analytical methods or analytical equipment used in the embodiments and comparative examples of the present invention:

[0069] X-ray diffraction pattern: Bruker D8 advance X-ray powder diffractometer was used.

[0070] SEM image: Regulus 8100 scanning electron microscope produced by Japan HITACHI Company was used; test conditions: after the sample was dried, vacuum evaporated to increase the conductivity and contrast effect, the acceleration voltage of the analysis electron microscope was 20.0kV, and the magnification was 30-110K.

[0071] TEM image: JEOL-JEM-2100F field emission transmission electron microscope was used; test conditions: the sample was dried and then evaporated in vacuum to increase the conductivity and contrast effect; the acceleration voltage of the analysis electron microscope was 20.0 kV, and the magnification was 1-20K.

[0072] Elemental analysis: The metal atom content in the molecular sieve was tested using an inductively coupled plasma atomic emission spectrometer (ICP-OES) from Varian, Germany. Before characterization, the sample was digested in an HF aqueous solution at room temperature.

[0073] Example 1

[0074] Tetraethyl orthosilicate, tetrapropylammonium hydroxide, palladium chloride-ethylenediamine complex solution and deionized water were mixed and stirred at 30°C for 8 hours to obtain a sol-gel, wherein the molar ratio of silicon element in tetrapropylammonium hydroxide and deionized water was 1:0.2:20, and the molar ratio of silicon element to palladium element was 1:0.0045.

[0075] The sol-gel obtained above was placed in a crystallization kettle, initially crystallized and nucleated at 80°C for 24 hours, then heated to 170°C for further crystallization for 72 hours, and centrifuged to obtain a solid.

[0076] The obtained solid was washed with water until neutral, dried at 100°C, heated to 500°C at a heating rate of 2°C / min, and calcined at this temperature for 10h, cooled to 40°C, heated to 400°C at a heating rate of 3°C / min, and reduced at this temperature and in a hydrogen atmosphere for 2h to obtain a catalyst. X-ray diffraction pattern is shown in Figure 1 , SEM and TEM images are shown in Figure 2 and Figure 3 .

[0077] Depend on Figure 1 It can be seen that the diffraction pattern shows that the catalyst is an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), and there is no characteristic diffraction peak corresponding to the palladium element, indicating that no large Pd particles are formed in the synthesized sample. Figure 2 and Figure 3 It can be seen that the morphology of the catalyst obtained in this embodiment is uniform, basically presenting a hexagonal prism, and the average linear size of its grains is 67nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated by the all-silicon molecular sieve, and the particle size is 1.7 to 3.0nm. According to elemental analysis, the content of metal Pd element in the catalyst is 0.91wt%, which is consistent with the theoretical feed.

[0078] Example 2

[0079] Except for the following parameters and settings, the rest are the same as Example 1: the molar ratio of silicon element to palladium element is 1:0.0025.

[0080] The X-ray diffraction pattern of the catalyst obtained in this embodiment shows that it is a full silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its crystal grains is 60nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 1.6 to 3.2nm. According to elemental analysis, the content of the metal Pd element in the catalyst is 0.42wt%, which is consistent with the theoretical feed.

[0081] Example 3

[0082] Except for the following parameters and settings, the rest are the same as Example 1: the complex solution of palladium chloride-ethylenediamine is replaced by the complex solution of rhodium chloride trihydrate-ethylenediamine.

[0083] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 4 As shown by Figure 4 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the rhodium element. The SEM and TEM results are shown in Figures 1 and 2. Figure 5 and Figure 6 .Depend on Figure 5 and Figure 6 It can be seen that the morphology of the catalyst obtained in this embodiment is uniform, basically presenting a hexagonal prism, and the average linear size of its grains is 76nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Rh nanoparticles are uniformly encapsulated, and the particle size is 1.4 to 2.7nm. According to elemental analysis, the content of metal Rh element in the catalyst is 0.87wt%, which is consistent with the theoretical feed.

[0084] Example 4

[0085] Except for the following parameters and settings, the rest are the same as Example 1: the palladium chloride-ethylenediamine complex solution is replaced by a chloroplatinic acid-ethylenediamine complex solution, and the molar ratio of silicon element to platinum element is 1:0.005.

[0086] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the platinum element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 79nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pt nanoparticles are uniformly encapsulated, with a particle size of 1.7 to 2.7nm. According to elemental analysis, the content of the metal Pt element in the catalyst is 0.96wt%, which is consistent with the theoretical feed.

[0087] Example 5

[0088] Except for the following parameters and settings, the rest are the same as Example 1: the palladium chloride-ethylenediamine complex solution is replaced by a copper nitrate trihydrate-ethylenediamine complex solution.

[0089] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the copper element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 76nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Cu nanoparticles are uniformly encapsulated, with a particle size of 2.1 to 3.5nm. According to elemental analysis, the content of metal Cu element in the catalyst is 0.91wt%, which is consistent with theoretical feeding.

[0090] Example 6

[0091] Except for the following parameters and settings, the rest are the same as Example 1: the palladium chloride-ethylenediamine complex solution is replaced with a nickel nitrate hexahydrate-ethylenediamine complex solution, and the molar ratio of silicon element to Ni element is 1:0.018.

[0092] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the nickel element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 80nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Ni nanoparticles are uniformly encapsulated, with a particle size of 2 to 4nm. According to elemental analysis, the content of metal Ni element in the catalyst is 3.74wt%, which is consistent with theoretical feeding.

[0093] Example 7

[0094] Except for the following parameters and settings, the rest are the same as Example 1: the time for initial crystallization nucleation is replaced with 48h.

[0095] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 83nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, with a particle size of 1.5 to 2.6nm. According to elemental analysis, the content of the metal Pd element in the catalyst is 0.88wt%, which is consistent with the theoretical feed.

[0096] Example 8

[0097] Except for the following parameters and settings, the rest are the same as Example 1: the molar ratio of silicon element to tetrapropylammonium hydroxide is 1:0.4.

[0098] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 69nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, with a particle size of 1.2 to 2.5nm. According to elemental analysis, the content of the metal Pd element in the catalyst is 0.90wt%, which is consistent with the theoretical feed.

[0099] Example 9

[0100] Except for the following parameters and settings, the rest are the same as Example 1: the time for continuing crystallization is replaced with 24 hours.

[0101] The X-ray diffraction pattern of the catalyst prepared in this example is as follows: Figure 7 As shown by Figure 7 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peak corresponding to the palladium element. The morphology of the obtained catalyst is uniform, basically presenting a hexagonal prism shape, and the average linear size of its grains is 88nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, with a particle size of 1.4 to 2.5nm. According to elemental analysis, the content of the metal Pd element in the catalyst is 0.90wt%, which is consistent with the theoretical feed.

[0102] Comparative Example 1

[0103] Except for the following parameters and settings, the rest are the same as Example 1: No palladium chloride-ethylenediamine complex solution is added. An all-silicon molecular sieve (ie, Silicalite-1 molecular sieve) is obtained.

[0104] The X-ray diffraction pattern of the all-silicon molecular sieve prepared in this comparative example is as follows Figure 8 As shown. Figure 8 It can be seen that the product is a full-silicon molecular sieve. The SEM analysis results are as follows Fig. 9 As shown by Fig. 9 It can be seen that the molecular sieve has a uniform morphology, which is basically a hexagonal prism, and the average linear size of its crystal grains is 70nm. Element analysis shows that there is no metal element and it is an all-silicon molecular sieve.

[0105] Comparative Example 2

[0106] The all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve) prepared in Comparative Example 1 was added to 20 ml of palladium chloride aqueous solution, and then stirred at room temperature for 5 hours to obtain a mixture, and the mixture was stirred in an 80°C water bath for 2 hours, and then placed in an oven at 105°C for drying for 20 hours, cooled, ground, calcined at 500°C for 10 hours, and then reduced at 400°C for 2 hours in a hydrogen atmosphere to obtain a catalyst. In the impregnation process, the molar ratio of silicon element in Silicalite-1 molecular sieve to palladium element in palladium chloride solution is 1:0.0045.

[0107] The X-ray diffraction pattern of the catalyst obtained in this comparative example is as follows Fig.10 As shown by Fig.10 It can be seen that in addition to the diffraction peaks of the all-silicon molecular sieve, there are also obvious characteristic diffraction peaks of metal Pd particles. The results of SEM and TEM analysis are shown in Figure 2. Fig.11 and Fig.12 As shown: the metal Pd particles are more distributed on the outer surface of the all-silicon molecular sieve.

[0108] Depend on Fig.12 It can be clearly seen that there are metal particles distributed on the surface at the top and rightmost edges. The surface is not smooth and there are some protruding metal particles.

[0109] contrast Figure 3 and Figure 5 It can be found that the catalyst obtained by the present invention has a smooth edge without protrusions, proving that the metal particles are distributed inside the molecular sieve rather than on the surface. This can also be confirmed from the reaction of benzaldehyde reductive amination: the metal particles of Comparative Example 2 are on the outside, and a large amount of dibenzylamine is obtained by the reaction, while the metal particles of the embodiment of the present invention are on the inside, and the pores will limit the generation of dibenzylamine macromolecules, and the product is mainly benzylamine.

[0110] Comparative Example 3

[0111] The only difference from the embodiment is that the amount of water used in the step of preparing the sol-gel is different, and the molar ratio of silicon element to water is 1:50.

[0112] The X-ray diffraction pattern of the catalyst obtained in this comparative example is as follows Fig.13 As shown by Fig.13 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peaks corresponding to palladium species. Fig.14 .Depend on Fig.14It can be seen that the morphology of the catalyst obtained in this comparative example is uniform, basically presenting a hexagonal prism, and the average linear size of its grains is 152nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 1.5 to 3.5nm. According to elemental analysis, the content of metal Pd element in the catalyst is 0.85wt%, which is consistent with the theoretical feed. In this comparative example 3, the crystal grains of the catalyst obtained are larger.

[0113] Comparative Example 4

[0114] The only difference from the embodiment is that the temperature of the initial crystallization nucleation is 110°C.

[0115] The X-ray diffraction pattern of the catalyst obtained in this comparative example is as follows Fig.13 As shown by Fig.13 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peaks corresponding to palladium species. Fig.15 .Depend on Fig.15 It can be seen that the morphology of the catalyst obtained in this comparative example is uniform, basically presenting a hexagonal prism, and the average linear size of its grains is 110nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 1.6 to 3.2nm. According to elemental analysis, the content of metal Pd element in the catalyst is 0.89wt%, which is consistent with the theoretical feed. The size of the crystal grains of the catalyst obtained in this comparative example 4 is relatively large.

[0116] Comparative Example 5

[0117] The only difference from the embodiment is that the step of preliminary crystallization nucleation is not performed.

[0118] The X-ray diffraction pattern of the catalyst obtained in this comparative example is as follows Fig.13 As shown by Fig.13 It can be seen that the diffraction pattern shows an all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve), without any characteristic diffraction peaks corresponding to palladium species. Fig.16 .Depend on Fig.16 It can be seen that the morphology of the catalyst obtained in this comparative example is uniform, basically presenting a hexagonal prism, and the average linear size of its grains is 330nm. The surface of the catalyst is smooth, without obvious granular substances. The metal Pd nanoparticles are uniformly encapsulated, and the particle size is 1.5 to 3.2nm. According to elemental analysis, the content of metal Pd element in the catalyst is 0.9wt%, which is consistent with theoretical feeding.

[0119] Experimental Example 1 - Reductive amination of furfural

[0120] The catalysts of Examples 1, 3 and Comparative Example 2 and the product of Comparative Example 1 were tested for catalyzing the reductive amination reaction of furfural.

[0121] The specific test conditions are as follows: the test process is carried out in a kettle reactor, the catalyst mass is 30 mg, the catalytic process conditions are as follows: the reaction pressure is 1.0 MPa, the molar ratio of hydrogen to furfural is 12.5:1, the molar ratio of ammonia to furfural is 400:1, the reaction temperature is 100°C, and the reaction time is 12 h.

[0122] Detection method: After the reaction, samples were collected and the product composition was analyzed by gas chromatography, and then the furfural conversion rate and tetrahydrofurfurylamine selectivity were calculated. The results are shown in Table 1.

[0123] The calculation formula of furfural conversion rate is: furfural conversion rate = [(mole number of furfural carbon in feed) - (mole number of furfural carbon in discharge)] ÷ (mole number of furfural carbon in feed) × 100%.

[0124] The calculation formula of the selectivity of tetrahydrofurfurylamine is: tetrahydrofurfurylamine selectivity = (carbon molar number of tetrahydrofurfurylamine in the discharge) ÷ (the total carbon molar number of all carbon-containing products in the discharge) × 100%.

[0125] Table 1

[0126]

[0127] As shown in Table 1, the all-silicon molecular sieve (i.e., Silicalite-1 molecular sieve) obtained in Comparative Example 1 has no catalytic activity for the reductive amination of furfural. The catalytic activity of the catalyst obtained in the embodiment of the present invention is significantly higher than that of the catalyst obtained by the impregnation method in Comparative Example 2. The catalyst obtained in the embodiment of the present invention has a high selectivity for tetrahydrofurfurylamine, which can reduce the cost of product separation and has obvious economic benefits.

[0128] Experimental Example 2 - Reductive amination of benzaldehyde

[0129] The catalysts of Examples 1 and 2 and Comparative Examples 2, 3, 4 and 5 were tested for catalyzing the reductive amination reaction of benzaldehyde.

[0130] The test method is as follows:

[0131] The test process was carried out in a kettle reactor with a catalyst mass of 20 mg and catalytic process conditions as follows: reaction pressure of 1.0 MPa, molar ratio of hydrogen to benzaldehyde of 12.5:1, molar ratio of ammonia to benzaldehyde of 500:1, reaction temperature of 50°C and reaction time of 3 h.

[0132] Detection method: After the reaction, samples were collected and the product composition was analyzed by gas chromatography, and then the conversion rate of benzaldehyde and the selectivity of benzylamine were calculated. The test results are shown in Table 2.

[0133] The conversion rate of benzaldehyde is calculated as follows: benzaldehyde conversion rate = [(the number of moles of benzaldehyde carbon in the feed) - (the number of moles of benzaldehyde carbon in the discharge)] ÷ (the number of moles of benzaldehyde carbon in the feed) × 100%.

[0134] The calculation formula of benzylamine selectivity is: benzylamine selectivity = (the molar number of carbon of benzylamine in the discharge) ÷ (the total molar number of carbon of all carbon-containing products in the discharge) × 100%.

[0135] Table 2

[0136]

[0137] As can be seen from Table 2, the catalyst obtained in the embodiment of the present invention has a higher conversion rate for benzaldehyde and a higher selectivity for benzylamine.

[0138] In addition, the catalyst obtained in Example 1 of the present invention has high stability. In the process of catalyzing the reductive amination of furfural or benzaldehyde, no obvious decrease in activity was observed even after three repeated uses. However, the catalyst described in Comparative Example 2 has poor stability and gradually deactivates as the catalytic reaction proceeds.

[0139] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.

Claims

1. A catalyst for the reductive amination of aldehydes and ketones, characterized in that: It includes all-silicon molecular sieve and metal particles; wherein, The metal particles are distributed inside the all-silicon molecular sieve; The average linear size of the catalyst crystals is 50 to 100 nm; The particle size of the metal particles is 0.5-4 nm; based on the mass of the catalyst, the mass percentage of the metal particles is 0.1-10wt%; the metal elements in the metal particles are selected from at least one of Pd, Pt, Rh, Cu, Ni, Co, Zn and Ag.

2. The catalyst according to claim 1, characterized in that The crystal grains of the catalyst are substantially in the shape of hexagonal prisms.

3. The catalyst according to claim 1, characterized in that The metal element in the metal particles is selected from one of Pd, Pt, Rh, Cu and Ni.

4. The method for preparing a catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) mixing a silicon-containing substance, alkylammonium hydroxide, a metal particle precursor and water and stirring at 20 to 45° C. to obtain a sol-gel; 2) Preliminarily crystallizing the obtained sol-gel at 70-100° C. to form nuclei, then heating to 160-180° C. to continue crystallization, and separating the solid and liquid to obtain a solid; 3) washing the obtained solid, drying it, calcining it at 500-600° C., and then reducing it in a hydrogen atmosphere at 350-450° C. to obtain the catalyst; in, The silicon-containing substance is selected from silicate or alkaline silica sol; the alkyl ammonium hydroxide is selected from at least one of tetramethyl ammonium hydroxide, tetraethyl ammonium hydroxide, tetrapropyl ammonium hydroxide, dimethyl diethyl ammonium hydroxide and dimethyl dipropyl ammonium hydroxide; the metal particle precursor is a water-soluble metal salt-ethylenediamine complex solution; The molar ratio of silicon element, alkylammonium hydroxide and water in the silicon-containing substance is 1:0.1-0.4:15-25; The molar ratio of the metal element in the water-soluble metal salt to the silicon element in the silicon-containing substance is 0.0004-0.055:

1.

5. The preparation method according to claim 4, characterized in that: The silicate is selected from at least one of methyl orthosilicate, ethyl orthosilicate, isopropyl orthosilicate and butyl orthosilicate.

6. The preparation method according to claim 5, characterized in that: The silicate is ethyl orthosilicate.

7. The preparation method according to claim 4, characterized in that: The alkylammonium hydroxide is tetrapropylammonium hydroxide.

8. The preparation method according to claim 4, characterized in that: The specific steps include: 1) mixing a silicon-containing substance, alkylammonium hydroxide, a water-soluble metal salt-ethylenediamine complex solution and water and stirring at 20 to 45° C. for 6 to 12 hours to obtain a sol-gel; 2) preliminarily crystallizing the obtained sol-gel at 70-100° C. for 24-48 hours to form nuclei, then heating to 160-180° C. to continue crystallization for 12-72 hours, and performing solid-liquid separation to obtain a solid; 3) washing the obtained solid, drying it, calcining it at 500-600° C. for 3-12 h, and then reducing it in a hydrogen atmosphere at 350-450° C. for 1.5-4 h to obtain the catalyst.

9. Use of the catalyst according to any one of claims 1 to 3 as a catalyst for the reductive amination of aldehydes and ketones.

10. The use according to claim 9, characterized in that: The aldehyde and ketone compounds include furfural and benzaldehyde; the target product of the reductive amination of furfural is tetrahydrofurfurylamine; and the target product of the reductive amination of benzaldehyde is benzylamine.

Citation Information

Patent Citations

  • Metal@Sillicalite-1 molecular sieve loading super-small noble metal particles, preparation method and application

    CN106669768A

  • Pure silicon S-1 molecular sieve catalyst for packaging metal nanoparticles and preparing method and application of catalyst

    CN109647493A

  • Noble metal-coated silicon molecular sieve catalytic material and preparation method thereof

    CN110116018A

  • Catalyst with non-noble metal nanoclusters confined and stabilized in silicalite-1 molecular sieve pore channels, and preparation method and application thereof

    CN110368982A

  • Alkaline molecular sieve supported catalyst and preparation method and application thereof

    CN111085247A

Cited By

  • Method for selectively preparing furan amine or tetrahydrofuran amine from furan aldehyde substance

    CN119874646A